1994
DOI: 10.1021/jo00096a042
|View full text |Cite
|
Sign up to set email alerts
|

Application of H-ZSM-5 Zeolite for Regioselective Mononitration of Toluene

Abstract: The nitration of toluene with n-propyl nitrate has been carried out in the presence of H-ZSM-5 as the catalyst. Several H-ZSM-5 catalysts with different Si/Al ratios were investigated to determine the influence of varying Si/Al ratios on the catalytic activity. It was found that high Si/Al ratios enhanced the regioselectivity for the p-nitrotoluene over the ortho isomer under comparable conditions. The best o:m:p product distribution (5:0:95) was achieved using H-ZSM-5 with a Si/Al ratio of 1000. The isolable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 0 publications
4
47
0
Order By: Relevance
“…The continuous flow vapour phase nitration using a solid acid catalyst has also been explored [26]. It is known that the solid acid catalysts, i.e., ZSM and other zeolite catalysts, can improve the selectivity of p -nitrotoluene in a conventional reactor using a mixed acid as the nitrating agent [5253]. Continuous flow nitration of toluene in a packed bed microreactor using concentrated nitric acid as the nitrating agent was reported by Halder et al [54].…”
Section: Reviewmentioning
confidence: 99%
“…The continuous flow vapour phase nitration using a solid acid catalyst has also been explored [26]. It is known that the solid acid catalysts, i.e., ZSM and other zeolite catalysts, can improve the selectivity of p -nitrotoluene in a conventional reactor using a mixed acid as the nitrating agent [5253]. Continuous flow nitration of toluene in a packed bed microreactor using concentrated nitric acid as the nitrating agent was reported by Halder et al [54].…”
Section: Reviewmentioning
confidence: 99%
“…One possible explanation is that the pore structures of the heterogeneous catalysts so produced are unsuitable as regards shape-selectivity for aromatic nitration [4,[22][23][24]. Further efforts to improve the regioselectivity of the supported M(NPf 2 ) n are underway.…”
Section: Nitration Of Toluene With Different Catalystsmentioning
confidence: 99%
“…In addition, such catalysts cannot be recovered any more. Therefore, lots of efforts had been directed to seek environmentally friendly and reusable alternatives in recent years [3][4][5][6][7][8][9][10][11][12][13][14]. In our previous work, we found that metal bis[(perfluoroalkyl)sulfonyl]imides (M(NPf 2 ) n , NPf 2 = N(SO 2 R f ) 2 and R f represents the perfluorinated alkyl group), a kind of novel Lewis acid, could catalyze nitration of some aromatic compounds in good to excellent yield [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the conventional industrial nitration, however, the production of the ortho-isomer exceeds that of the para-isomer. To overcome this limitation, various nitration systems using solid acids as catalysts were investigated [2][3][4][5][6][7][8]. Of particular interest is the high para-selectivity achieved with zeolite BEA and the combination of nitric acid and acetic anhydride as a nitrating agent, as reported initially by Smith et al [4,9] and later investigated in our laboratory [10,11].…”
Section: Introductionmentioning
confidence: 99%